Decoupage Finishing Techniques for Home Decor Elements - Dyan Agustin (Nusantara Science and Technology Proceedings, 2021)
Decoupage is an art of decoration by sticking pieces of paper on the surface of objects with glue media. This decoupage finishing technique can be used in many elements of home decor, it is easy to teach and the materials are easy to get. Therefore, this finishing technique was chosen as a service activity to train PKK women in RT 6 RW 2 Lowokwaru Malang which is close to several tourist sites. The method used in this training is counseling on how to sell decoupage products and training on making products with the decoupage application. At this stage, examples of good creative product designs are also shown to explore creativity in the context of making products later. The types of products made include wall decoration products, pandan wallets, cake jars, etc. With this service activity, it is hoped that it can improve the skills of PKK members in the village so that they can increase household income and make RT 6 RW 02 Lowokwaru Malang a tourist village.